THE EFFECT OF CAREER DEVELOPMENT AND WORK MOTIVATION ON EARLY PENSION DESIRE - B Medina Nilasari (Universitas Trisakti, 2018)
In this study, we will examine the effect of Career Development and Work Motivation on the Desire of Early Retirement. The proposed hypothesis was tested with a sample of 150 employees in Trisakti University. Testing of research problems shows that Career Development has a positive influence on employee Motivation. Whereas Work Motivation has a negative influence on the Desire for Early Retirement of employees. However Career Development does not have a negative influence on the Desire for Early Retirement of employees. But work motivation as a mediating variable increases the negative influence of Career Development on the Desire of Early Retirement of employees.